Assessment of coastal water productivity of Fitu Village, Ternate Island based on its zooplankton community structure. Issue 1 (October 2021) - Yuliana,; Mutmainnah,
Abstract: Zooplankton has an important role in waters, especially in the food chain, this organism is the first consumer that plays a major role in bridging the transfer of energy from the main producers to living things at a higher trophic level. The aim of the study was to analyze the coastal waters condition of Fitu Village, Ternate Island based on zooplankton community structure, carried out at 4 stations, and 4 sampling periods. Zooplankton samples were taken by filtering method. The results showed that there were 10 zooplankton genera from 4 classes, namely Ciliates (3 genera), Crustacea (4 genera), Hydrozoa (1 genus), and Rotifera (2 genera). The abundance of zooplankton found ranged from 2271 to 11562 ind.l −1, the highest at station 1 period IV and the lowest at station 4 period I. The value range of zooplankton biological indices were diversity index (H') = 1.12 - 1.87, evenness index (E) = 0.64 - 0.93, and the dominance index (D) = 0.17 - 0.42. The waters of Fitu are included in the category of waters that have a low fertility level with a diversity index value (H') of 1.12 - 1.87.